2016
DOI: 10.5536/kjps.2016.43.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Corn with Rice or Brown Rice on Laying Performance, Egg Quality, and Apparent Fecal Digestibility of Nutrient in Hy-Line Brown Laying Hens

Abstract: This study aimed of effects of replacing maize with rice or brown rice on laying performance, egg quality, and apparent fecal digestibility of nutrient in Hy-Line Brown laying hens. A total of 200, 25-week old Hy-Line Brown laying hens were randomly assigned to one of 5 treatments, each of which was replicated 4 times. Four experimental diets that were formulated two different grains (brown rice or rice) with two inclusion levels of (15 and 30%) as a replacement of maize. The experimental period was 8 weeks. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…In Exp. 1, the GE content was in agreement with the values (3,831 and 3,800 kcal/kg on an as-fed basis) reported by Asyifah et al [4] but was much greater than the value (3,248 kcal/kg on an as-fed basis) reported by Kim et al [12]. The reason for this discrepancy is unclear.…”
Section: Discussionsupporting
confidence: 88%
“…In Exp. 1, the GE content was in agreement with the values (3,831 and 3,800 kcal/kg on an as-fed basis) reported by Asyifah et al [4] but was much greater than the value (3,248 kcal/kg on an as-fed basis) reported by Kim et al [12]. The reason for this discrepancy is unclear.…”
Section: Discussionsupporting
confidence: 88%